Electric Vehicle Charging at the Workplace: Experimental Evidence on Incentives and Environmental Nudges - Teevrat Garg; Ryan Hanna; Jeffrey Myers; Sebastian Tebbe; David G. Victor (CESifo GmbH, 2024)
To minimize the environmental costs of electric vehicles (EVs) and support decarbonizing electric grids, drivers must charge their EVs when renewable energy generation is abundant. To induce a shift in charging behavior toward daytime hours with ample solar energy, we conducted a field experiment (n = 629) at a large workplace to measure the influence of environmental nudges and financial incentives on the usage and timing of workplace charging. Environmental nudges led drivers to shift from early to later morning charging, whereas discounts to charge at work increased total workplace charging and prompted a shift from daytime to early morning and overnight charging. We identify three clusters of mechanisms explaining these temporal shifts: the utilization and reliability of the charging network, concerns about charger scarcity, and driver characteristics. Finally, we compute the societal effects of CO2 emissions and marginal electricity costs of these shifts in workplace charging sessions.
Keywords: 330